Predictive Risk Factors of Smartphone Addiction in Adolescents: A Systematic Review - Abdul Fauzi; Ah Yusuf; Mundakir Mundakir (Universitas Airlangga, 2019)
Introduction: Smartphone addiction often occurs in adolescents. The purpose of this systematic review was to identify the predictors of smartphone addiction in adolescents.Methods: The method used in this systematic review consisted of 5 stages: (1) the identification of the instruments used in the literature (database search); (2) the identification of the relevant literature based on the title and abstract; (3) the inclusion and exclusion criteria; (4) getting the full-text literature and (5) grading based on the literature component and the analysis of the selected instruments. The databases used in the literature search were Scopus, PubMed, Science Direct and Springer Link from 2013 - 2018. The criteria for the included articles were that they used a cross-sectional design and involved adolescents as the sample.Results: 17 of 829 articles met the inclusion criteria. The predictors of smartphone addiction were broadly divided into 3, namely personal factors, interpersonal factors and behavioral factors. These 3 factors are related to one another.Conclusion: It is necessary to do further research within a case-control study to strengthen this systematic review.